Linking transitions and sustainability: A study into social effects of transition management - Niko Schäpke; Ines Omann; Julia Wittmayer; Frank van Steenbergen; Mirijam Mock (Helmholtz-Zentrum für Umweltforschung (UFZ), 2016)
Sustainability transitions as processes of fundamental change in societal systems are open-ended, nonlinear and uncertain. Respective research and governance approaches, e.g. transition management, propose a reflexive way of governing, aiming for a number of social effects to help facilitating a transition. Effects include empowerment, social learning and social capital development. Jointly mentioned social effects shall allow for reflexivity and innovation in developing socially robust and contextualized solutions to sustainability challenges that work in practice. Still, understanding mentioned social effects and their interplay more in depth is needed to design and assess transition management processes. While such understanding and related assessment framework is under development in transition management literature, transdisciplinary sustainability research can provide a rich body of tools and experiences. Building on a review of respective literature, this article develops an evaluation framework focusing on social effects as important and hitherto under conceptualised aspects of sustainability transitions literature. This framework is used to empirically investigate the effects of two specific transition management processes at local scale. Doing so, the article provides a conceptual and empirical understanding of how social effects contribute to a transition towards sustainability. Results highlight the importance and possibilities of addressing sustainability as an inherent quality of social effects aimed for.
Keywords: 330; assessment; case study; empowerment; social capital; social effects; social learning; sustainability transition; transition management; sustainability transformation